(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction-Suicide is a tragic and complex phenomenon that poses significant challenges to individuals, families, and societies worldwide. One distressing method that individuals may employ in their desperate act is suicide by corrosive acid. The Corrosive, Aqua regia, an extremely corrosive mixture of nitric acid and hydrochloric acid when used as a method of self-inflicted harm involves the deliberate ingestion or exposure to it, leading to severe injuries and often fatal consequences. This is the rare autopsy report representing the findings in case of suicidal death due to aqua regia.Aim To present an autopsy case of Suicidal death due to Aqua regia ingestion.Case report-we present a case of death due to aqua regia ingestion. It was a hospital death showing death due to corrosive ingestion, the burn percentage was near 60%. On external examination exposed surface was yellowish-brown in color. On internal examination, the abdominal cavity was filled with blood. Besides severe congestion, perforation, and brownish-black discoloration were present. Conclusion-Suicide by corrosive acid represents a distressing and complex issue that requires careful examination. The highly corrosive nature of aqua regia can cause severe damage to the GI tract, particularly the oral cavity, oesophagus, stomach and intestine. This Tragic case highlights the importance of early identification, intervention and support for individuals at risk of self-harm.